Eosinophilic Ureteritis: Report of A Rare Case - Asad, Hafiz Al; Belal, Md Towhid; Islam, Md Kamrul; Saha, Produyt Kumar (Journal of Surgical Sciences, 2019)
During evaluation for left loin to groin pain, a 14- year-old boy was found to have left mid ureteric stricture with proximal hydro-ureteronephrosis on imaging. Pus cells were present in his urine with a raised serum creatinine level. There was peripheral eosinophilia and biopsy near the stricture revealed eosinophilic ureteritis. The patient was evaluated to find out the possible causes of eosinophilia. Here we report a case of eosinophilic ureteritis for its rarity. Journal of Surgical Sciences (2015) Vol. 19 (2) : 80-81